The relationship between social capital and income generation amongst Indians in South Africa : an exploratory and comparative study in post-Apartheid South Africa - Schulein, Stefanie (Stellenbosch : Stellenbosch University, 2012)
Thesis (MPhil)--Stellenbosch University, 2005.